A stylized computational model of the head for the reference Japanese male - Yamauchi, M.; Ishikawa, M.; Hoshi, M. (Medical Physics, 2005)
Computational models of human anatomy, along with Monte Carlo radiation transport simulations, have been used by Snyder et al. [MIRD Pamphlet No. 5, revised (The Society of Nuclear Medicine, New York, 1978)], Cristy and Eckerman [ORNL/TM-8381/VI, Oak Ridge National Laboratory, Oak Ridge, TN (1987)] and Zubal et al. [Med. Phys. 21, 299–302 (1994)] to estimate internal organ doses from internal and external radiation sources. These were created using physiological data from Caucasoid subjects but not from other races. There is a need for research to determine whether the obvious differences from the Caucasoid anatomy make these models unsuitable for estimating the absorbed dose in other races such as the Mongoloid. We used the cranial region of the adult Japanese male to represent the Mongoloid race. This region contains organs that are highly sensitive to radiation. The cranial region of a physical phantom produced by KYOTO KAGAKU Co., LTD. using numerical data from a Japanese Reference Man [Tanaka, Nippon Acta. Radiol. 48, 509–513 (1988)] was used to supply the data for the geometry of a stylized computational model. Our computational model was constructed with equations rather than voxel-based, in order to deal with as small a number of parameters as possible in the computer simulation experiment. The accuracy of our computational model was checked by comparing simulated experimental results obtained with MCNP4C with actual doses measured with thermoluminescence dosimeters (TLDs) inside the physical phantom from which our computational model was constructed. The TLDs, whose margin of error is less than ± 10 % , were arranged at six positions. Co-60 was used as the radiation source. The irradiated dose was 2 Gy in terms of air kerma. In the computer simulation experiments, we used our computational model and Cristy’s computational model, whose component data are those of the tissue substitute materials and of the human body as published in ICRU Report 46. The observed absorbed dose values (Gy) at all six points were calculated as the percentage difference between MCNP4C simulation and the TLDs. In our computational model, the average values of all the percentage differences were 6.0 ± 4.0 % (tissue substitute materials) and 7.6 ± 6.6 % (ICRU Report 46), respectively. In Cristy’s model, the corresponding values were 20.4 ± 3.8 % (tissue substitute materials) and 21.0 ± 4.1 % (ICRU Report 46), respectively. Considering the margin of error in the radiation sensitivity of the TLDs, this study validates our computational model as a test object for radiation dosimetry studies.